6,7-Dimethoxy-2-phenethyl-1,2,3,4-tetrahydroisoquinoline amides and corresponding ester isosteres as multidrug resistance reversers - Laura Braconi; Gianluca Bartolucci; Marialessandra Contino; Niccolò Chiaramonte; Roberta Giampietro; Dina Manetti; Maria Grazia Perrone; Maria Novella Romanelli; Nicola Antonio Colabufo; Chiara Riganti; Silvia Dei; Elisabetta Teodori (Taylor & Francis Group, 2020)
Aiming to deepen the structure-activity relationships of the two P-glycoprotein (P-gp) modulators elacridar and tariquidar, a new series of amide and ester derivatives carrying a 6,7-dimethoxy-2-phenethyl-1,2,3,4-tetrahydroisoquinoline scaffold linked to different methoxy-substituted aryl moieties were synthesised. The obtained compounds were evaluated for their P-gp interaction profile and selectivity towards the two other ABC transporters, multidrug-resistance-associated protein-1 and breast cancer resistance protein, showing to be very active and selective versus P-gp. Two amide derivatives, displaying the best P-gp activity, were tested in co-administration with the antineoplastic drug doxorubicin in different cancer cell lines, showing a significant sensitising activity towards doxorubicin. The investigation on the chemical stability of the derivatives towards spontaneous or enzymatic hydrolysis, showed that amides are stable in both models while some ester compounds were hydrolysed in human plasma. This study allowed us to identify two chemosensitizers that behave as non-transported substrates and are characterised by different selectivity profiles.